Markerless detection of fingertips of object-manipulating hand - Sophian, Ali; Awang Za’aba, Dayang Qurratu’aini; Sediono, Wahju; Md. Yusof, Hazlina; Sudirman, Sud (Asian Research Publishing Network (ARPN), 2016)
Most reported works on fingertip detection focus on extended fingers where the hand is not occluded by another object. This paper proposes a machine-vision-based technique exploiting the contour of the hand and fingers for detecting the fingertips when the hand is manipulating a ball, which means that the fingers are closed and the hand is partially occluded. The preliminary result of our on-going research is promising where it can be used to generate a more objective performance indicator for monitoring the progress during hand therapy by using a digital webcam. Being markerless and contactless, the proposed technique will require minimal preparation prior to the therapy.